Artificial neural network tactic to predict interest in majors in computing. (5th September 2022) - Idwan, Sahar; Ismail, Shereen; Ashhab, Moh'd Sami; Awad, Mohammed; Matar, Izzeddin
In this paper, we will present the first study of using the neural network approach to predict aspects that influence high school students in selecting an information and communication technology (ICT) related major at their respective universities. A survey was distributed among high school students to determine the factors towards choosing related fields in ICT. We trained the neural network algorithm with the available data. The input to the network stems from six factors: curriculum, extra-curricular activities, decision-makers, teachers, importance of ICT or computing-related subjects at school, and infrastructure. The neural network predicts the high school student's behaviour towards choosing the ICT major at the university level. Simulation results show the importance of these factors in predicting the student's choice in majoring in ICT.